MULTIPLE PERSONALITY. DISSOCIATION MECHANISM OPPOSITE TO SCHIZOPHRENIA - Georgiana, Dinu Lorena; Ruxandra, Toma; Popa, Ionuţ; Trifu, Simona (International Journal of Research -GRANTHAALAYAH, 2021)
Motivation: identity disorder is a mental disorder with a major impact on all aspects of a person’s life, affecting in many cases most of its functional areas. The patient in this case study is 40 years old and appears to have good functionality at work, but his personal life is affected. As co-morbid disorders, obsessive-compulsive disorder and substance use can be mentioned. On the other hand, making a differential diagnosis between identity disorder and schizophrenia is difficult for this patient, because he has symptoms with elements specific for both disorders. Objectives: This paper aims to assess the current profile and longitudinal dynamics of a identity disorder in the case of a 40-year-old patient. He was brought to the psychiatrist by his sister, who found some quirks in his brother’s behavior and insisted that he consult a specialist to help him. Also, considering the stress-vulnerability model, the factors that contributed to the onset of the pathology will be captured. Simultaneously with the symptoms of this disorder, we will also consider the effects that substance use has on the patient’s condition. Methods: Psychological evaluation, interview, case study, management of the therapeutic alliance and proposal of a long-term treatment, in the absence of which the symptoms may worsen, with the risk of significantly affecting functionality and even suicide. Results: The study outlines a profile based on the fragility of the ego and personal boundaries, going as far as the splitting of the ego, the patient declares that there are different people in it: "authority, accountant, good will", "Half of the things I say I hear for the first time"), the fragility of the boundaries of reality ("life is not reality", "to stay away from reality and stay in my mind for a while"), confusion between the material area and the immaterial one ("the bottom step of the safety pyramid", "I don’t clean the house because it costs; at first it costs detergents and then it costs the mind to force itself to clean it too"), dissociation between body, mind and soul ("I speak with my desires", "the body was born first, I was born after; the desires are his"), chain of ideas and flight of thoughts, to which are added behaviors from the obsessive-compulsive spectrum (" mistakes are a kind of death "," I am not allowed to spend, not for me either ”,“ 10 pairs of socks. Do you have? We are not talking”)